Citrus Mechanical Harvesting Systems--Trunk Shakers - Fritz M. Roka; Reza J. Ehsani; Stephen H. Futch; Barbara R. Hyman (EDIS, 2014)
While citrus growers are rightfully concerned about restoring the health of their HLB-infected trees, more study and consideration should be given to mechanical harvesting. The costs to grow and harvest citrus have been escalating significantly since 2006, and the cost savings potential from mechanical harvesting technologies can help Florida growers remain economically viable. This 4-page fact sheet was written by F.M. Roka, R.J. Ehsani, S.H. Futch, and B.R. Hyman, and published by the UF Department of Food and Resource Economics, August 2014.